Transition Engagement of African American Youth With Disabilities: A Serial Mediation Model. (April 2020) - Dutta, Alo; Kundu, Madan; Iwanaga, Kanako; Ditchman, Nicole; Chan, Fong
The purpose of this study was to draw from self-determination and self-efficacy theories to evaluate psychological constructs (autonomous motivation, competency, and outcome expectancy) as mediators of the relationship between working alliance and engagement in transition–vocational rehabilitation (VR) services among African American students with disabilities. A serial multiple mediation analysis was computed to evaluate the mediators of transition-VR service engagement in a sample of 88 African American high school students with disabilities. We found that working alliance was positively associated with active engagement in transition-VR services (total effect), whereas the direct effect of working alliance on engagement was not significant after controlling for the effects of autonomous motivation, competency, and outcome expectancy, supporting significant mediation effects. Findings suggest that a strong working alliance between students and rehabilitation counselors and transition specialists can foster autonomous motivation, competency, and outcome expectancy, resulting in higher levels of engagement in transition-VR services.